Republic of Tajikistan : Evaluation of the Poverty Reduction Strategy Paper Process and Arrangements Under the Poverty Reduction and Growth Facility - International Monetary Fund; World Bank (Washington, DC, 2014)
The International Monetary Fund (IMF) and the World Bank introduced the Poverty Reduction Strategy Paper (PRSP) process in 1999 to strengthen the poverty alleviation focus of their assistance to low-income countries. This report reviews Tajikistan s experience with the PRSP process, focusing on the effectiveness of IMF and World Bank support to the process and the extent to which the two institutions lending and non-lending activities in the country are aligned to the objectives of the PRSP approach. The rest of the report is organized as follows. Part two provides brief background accounts of political and economic developments since independence in 1991, including poverty incidence in the late 1990s. The relevance of the PRSP approach, application of the underlying principles, and preliminary evidence on results, are examined in part three. Part four considers the effectiveness of World Bank support, including alignment of that support to the objectives of the PRSP approach. The effectiveness of IMF support, including alignment of programs supported under the Poverty Reduction and Growth Facility (PRGF) and its predecessor, the Enhanced Structural Adjustment Facility (ESAF), to PRSP objectives, is assessed in part five. Part six reviews IMF-World Bank collaboration, include the Joint Staff Assessments (JSA) of the PRSP and of collaboration on country operations. Part seven presents main conclusions and lessons.